The Satirical Language Style and Critical Reasoning Values in the YouTube Video 'Santoon TV' and Their Relevance to the Learning of Anecdotal Texts for Class X: Gaya Bahasa Satire dan Nilai Bernalar Kritis dalam Video YouTube “Santoon TV” serta Relevansinya pada Pembelajaran Teks Anekdot Kelas X - Intan Wulan Sari; Deby Luriawati Naryatmojo (Anthology: Journal of Language, Literature, and Learning, 2025)
This research examines the types of satirical language styles and critical reasoning values found in the YouTube video "Santoon TV," as well as their relevance to teaching anecdotal texts to tenth-grade students. The objective of this study is to describe the types of satirical language styles and critical reasoning values in the YouTube video "Santoon TV," along with its relevance to the teaching of anecdotal texts for tenth graders. The method employed in this research is a descriptive method with a qualitative approach. The data collection techniques used are free listening, conversational engagement, and note-taking. The data analysis technique in this study utilizes an interactive model, encompassing data collection, data reduction, data presentation, and conclusion drawing. The research findings from the YouTube video "Santoon TV" are relevant to the learning of anecdotal texts as it contains two types of satirical language styles, namely Horatian and Juvenalian, which are interesting for students to study as material content for anecdotal texts. The critical reasoning values present in the YouTube video "Santoon TV" also comprehensively encompass the three elements, making it beneficial for enhancing the Pancasila Student Profile among learners. Furthermore, the YouTube video "Santoon TV" meets the criteria for a learning resource, being practical, economical, easy, flexible, and aligned with the learning objectives of anecdotal texts for grade X high school. It is hoped that the results of this research will broaden insights and assist educators in selecting innovative learning resources for anecdotal texts.   Penelitian ini menganalisis jenis gaya bahasa satire dan nilai bernalar kritis yang terdapat dalam video YouTube “Santoon TV”, serta relevansinya terhadap pembelajaran teks anekdot kelas X. Tujuan penelitian ini adalah mendeskripsikan jenis gaya bahasa satire dan nilai bernalar kritis dalam video YouTube “Santoon TV”, serta relevansinya terhadap pembelajaran teks anekdot kelas X. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan adalah simak bebas libas cakap dan catat. Teknik analisis data dalam penelitian ini menggunakan model interaktif mulai dari pengumpulan data, reduksi data, penyajian data, hingga penarikan simpulan. Hasil penelitian video YouTube “Santoon TV” memiliki relevansi dengan pembelajaran teks anekdot karena memuat dua jenis gaya bahasa satire, yaitu horation dan juvenalian yang menarik untuk dipelajari peserta didik sebagai muatan materi teks anekdot. Nilai bernalar kritis yang terdapat dalam video YouTube “Santoon TV” juga lengkap memuat ketiga elemen sehingga bermanfaat untuk meningkatkan Profil Pelajar Pancasila pada peserta didik. Selain itu, video YouTube “Santoon TV” juga memenuhi kriteria sebagai sumber belajar, yaitu praktis, ekonomis, mudah, fleksibel, dan sesuai dengan tujuan pembelajaran teks anekdot kelas X SMA. Hasil penelitian ini diharapkan dapat menambah wawasan dan membantu pendidik dalam memilih sumber belajar teks anekdot yang inovatif.